Management of sadaqah fund at mosques: a case study in Shah Alam, Selangor / Hikmah Abd Rahim - Abd Rahim, Hikmah (2018)
This research is for make an analysing about the sadaqah fund management of the several mosques that have in Shah Alam, Selangor. This study aim to know with detail about the fund management of mosques in Shah Alam annually since 2014 until now. Nowadays, we have familiar with some problems about sadaqah fund management of the mosques like lack of sadaqah fund management, lack of activity, lack of sources of income and the others. This research have been done based on several methodology resources from document analysis and field study. From the document analysis will collect data and information from the books, journals, articles and internets about fund management of mosque while from the field study get the information from several respondent of the mosque committees include mosque officers like Imam, Bilal, Treasurer and the other. Based on results and finding in this research will find how several mosques at Shah Alam manage in mosques sadaqah fund as the role model to the other mosques. Keywords: Fund, Mosques, Shah Alam.